THE FEASIBILITY OF THE CUKU NYINYI MANGROVE FOREST TOURIST ATTRACTION OBJECT IN SIDODADI VILLAGE, PESAWARAN DISTRICT - Nandita Aisha, Nandita Aisha; Sugeng Prayitno Harianto; Hari Kaskoyo (Jurnal Belantara, 2025)
The feasibility of tourist attractions in mangrove forests can create good economic opportunities, increase regional income and expand employment opportunities for surrounding residents. This study aims to analyze the feasibility of tourist attractions in the Cuku Nyinyi Mangrove Forest. Data collection is in the form of a survey by distributing questionnaires to tourists. Data analysis uses a scoring method based on the Guidelines for Analysis of Operational Areas of Natural Tourism Objects and Attractions of the Directorate General of PHKA in 2003. The results of the study showed that the attraction received a feasibility index of 78%, accessibility 86%, amenities 75% and additional services 85% so that the overall average is 81% which is included in the category of feasible to be developed. The level of feasibility of the four components shows that it is feasible to be developed, but there are still some shortcomings that need to be further developed in each component.